2018
DOI: 10.1177/0003489418792939
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and Description for Congenital Middle Ear Malformations to Facilitate Surgical Management

Abstract: The authors describe the different types of congenital middle ear malformations. This category description considers ear embryogenesis and is focused on stapes deformity. It may provide better understanding of disease development and guide modern hearing reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…16,17 However, a few studies reported that the incus anomaly was predominant in their case series. [18][19][20] Other studies 5,21 have identified stapes and incudostapedial complex as the most commonly involved structure. In our study, isolated anomalies of the stapes and anomalies of the incus associated with the stapes contributed to the majority of the malformations found in surgery (29.0% and 50.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 However, a few studies reported that the incus anomaly was predominant in their case series. [18][19][20] Other studies 5,21 have identified stapes and incudostapedial complex as the most commonly involved structure. In our study, isolated anomalies of the stapes and anomalies of the incus associated with the stapes contributed to the majority of the malformations found in surgery (29.0% and 50.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Yang [8] reviewed 41 articles with 662 cases published between 2000 and 2017 and reported that only 17 out of 189 cases with atresia of the oval window or a fixed stapes footplate demonstrated normal stapes superstructure. In a study of 97 ears with a missing oval window, no cases showed normal stapes, suggesting that the defects in the stapes were closely correlated with the absence of the oval window [9].…”
Section: Discussionmentioning
confidence: 99%
“…12 Though more recently, it is suggested that type 3 anomalies occur most often. [13][14][15][20][21][22] In contrast to results in CMEA class 1 to 3 anomalies, surgery performed on class 4 anomalies has resulted in mixed long-term outcomes in several studies due to iatrogenic hearing loss and re-obliteration of the newly created window to the inner ear. 17,23,24 Also, in several studies it is suggested that middle ear surgery in patients with specific syndromes can be less effective to restore hearing than in non-syndromal patients.…”
Section: Introductionmentioning
confidence: 99%